First-line pembrolizumab/placebo plus trastuzumab and chemotherapy in HER2-positive advanced gastric cancer: KEYNOTE-811 - Chung, Hyun Cheol; Bang, Yung-Jue; S Fuchs, Charles; Qin, Shu-Kui; Satoh, Taroh; Shitara, Kohei; Tabernero, Josep; Van Cutsem, Eric; Alsina, Maria; Cao, Zhu Alexander; Lu, Jia; Bhagia, Pooja; et al. (Future oncology (London, England), 2021)
Treatment options for patients with HER2-positive advanced gastric cancer are limited, and the prognosis for these patients is poor. Pembrolizumab has demonstrated promising antitumor activity in patients with advanced gastric or gastroesophageal junction adenocarcinoma as monotherapy, in combination with chemotherapy and in combination with trastuzumab. Combining pembrolizumab with trastuzumab and chemotherapy may therefore provide a benefit for patients with advanced HER2-positive gastric cancer. Here we aimed to describe the design of and rationale for the randomized, double-blind, placebo-controlled Phase III KEYNOTE-811 study, which will evaluate the efficacy and safety of pembrolizumab or placebo in combination with trastuzumab and chemotherapy as first-line treatment for patients with advanced HER2-positive gastric or gastroesophageal junction adenocarcinoma. Clinical trial registration: NCT03615326 ( )